2013
DOI: 10.1007/s00268-013-2073-y
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Surgery Clerkship and the Choice of Surgery as a Career: Perspective from a Developing Country

Abstract: Periodic assessment of the satisfaction of medical students regarding their surgical clerkship experience is important. In our setting, we have identified aspects of the surgical clerkship that could be improved to enhance the quality of the experience, ensure the attractiveness of the field to the most qualified candidates, and boost interest in surgery as a career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…Of these studies, 11 showed that clinical exposure improves student knowledge of and interest in surgery. [55][56][57][58][59][60][61][62][63][64][65] Clerkship changed student perception of surgery and the surgical lifestyle in 6 of the studies we identified. [66][67][68][69][70][71] This has a variable impact on student interest in a surgical career.…”
Section: Clinical Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 11 showed that clinical exposure improves student knowledge of and interest in surgery. [55][56][57][58][59][60][61][62][63][64][65] Clerkship changed student perception of surgery and the surgical lifestyle in 6 of the studies we identified. [66][67][68][69][70][71] This has a variable impact on student interest in a surgical career.…”
Section: Clinical Exposurementioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63][64][65] Specifically, students with early interest in surgery were more likely to seek out surgical experiences and were more inclined to report a positive clerkship experience, thereby artificially strengthening the association be tween exposure and interest.…”
Section: Limitationsmentioning
confidence: 99%
“…Seen as an essential skill required for learner improvement, effective feedback may support the learner in accomplishing defined goals 29. In one of a few studies evaluating perceptions of undergraduate surgical training amongst medical students in the developing world, a study from Nigeria30 reported that just over half of students believed that feedback on their performance was adequate. The current study found UCT faculty to be significantly more consistent in evaluating students when compared to KI faculty.…”
Section: Discussionmentioning
confidence: 99%
“…1 Departments try to counteract this decline by improving their teaching, as positive experience is regarded to increase students' interest to pursue a surgical career. [2][3][4] This renewed interest in surgical education has led to an increasing amount of educational research in this field. Resulting studies have revealed significant gaps in clinical exposure during surgical clerkships.…”
Section: Introductionmentioning
confidence: 99%